Specificity and sensitivity of the SeLECT score in predicting late seizures in patients undergoing intravenous thrombolytic treatment and the effect of diabetes mellitus and leukoaraiosis - Yasemin Dinç; Aylin Bican Demir; Güven Özkaya; Mustafa Bakar (Arquivos de Neuro-Psiquiatria)
Background Seizures after stroke can negatively affect the prognosis of ischemic stroke and cause a decrease in quality of life. The efficacy of intravenous (IV) recombinant tissue plasminogen activator (rt-PA) treatment in acute ischemic stroke has been demonstrated in many studies, and IV rt-PA treatment has been increasingly used around the world. The SeLECT score is a useful score for the prediction of late seizures after stroke and includes the severity of stroke (Se), large artery atherosclerosis (L), early seizure (E), cortical involvement (C), and the territory of the middle cerebral artery (T). However, the specificity and sensitivity of the SeLECT score have not been studied in acute ischemic stroke patients that received IV rt-PA treatment.